Momma and the meaning of life : tales of psychotherapy - Yalom, Irvin D., 1931- (London : Piatkus, 2006)
This classic medium, first popularised by Freud and, more recently, by Oliver Sacks and Yalom himself, provides a fascinating insight into the human condition and our search for happiness. Contains six absorbing case studies which reveal the intricacies our psychological landscapes. Provides a fascinating insight into the human condition and our search for happiness. Explores the unique dynamic of the relationship between therapist and client. Absorbing and deeply thoughtful, Momma and the Meaning of Life is a work of rare insight and imagination.
Psychotherapie